2010
DOI: 10.1002/chem.200902546
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effect of Surface Ligands on Dendron–DNA Interactions: Insights into Multivalency through a Combined Experimental and Theoretical Approach

Abstract: We report the synthesis, DNA binding ability and preliminary gene delivery profiles of dendrons with different amine surface groups, 1,3-diaminopropane (DAP), N,N-di-(3-aminopropyl)-N-(methyl)amine (DAPMA) and spermine (SPM). By using a combination of ethidium bromide displacement, gel electrophoresis and transfection assays, it is shown that the dendrons with SPM groups are the most effective DNA binders, while the DAPMA-functionalised dendrons were the most effective systems for gene delivery (although the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 157 publications
3
41
0
3
Order By: Relevance
“…Importantly, in the absence of any hydrophobic modification, the G2 dendron 65 is incapable of effective DNA binding (data not shown) -and as such, SAMul plays a key role in all of the binding discussed. For the disulfide-linked G2 dendrons, the system with less hydrophobic modification is a more effective DNA binder -this is in agreement with the experimental and simulated zeta 75 potential results (Tables 1 and 2) which indicated that the hydrophobic/hydrophilic balance of Chol-SS-G2 is such that it has a higher surface charge density than Chol 2 -SS-G2. However, it should also be noted that Chol-G2 is better than the degradable dendrons in the EthBr assay, and comparable to the best in gel 80 electrophoresis.…”
Section: Dna Binding Studiessupporting
confidence: 87%
See 1 more Smart Citation
“…Importantly, in the absence of any hydrophobic modification, the G2 dendron 65 is incapable of effective DNA binding (data not shown) -and as such, SAMul plays a key role in all of the binding discussed. For the disulfide-linked G2 dendrons, the system with less hydrophobic modification is a more effective DNA binder -this is in agreement with the experimental and simulated zeta 75 potential results (Tables 1 and 2) which indicated that the hydrophobic/hydrophilic balance of Chol-SS-G2 is such that it has a higher surface charge density than Chol 2 -SS-G2. However, it should also be noted that Chol-G2 is better than the degradable dendrons in the EthBr assay, and comparable to the best in gel 80 electrophoresis.…”
Section: Dna Binding Studiessupporting
confidence: 87%
“…It was therefore clear from these MS studies that over a 24 hour timescale, all three dendrons degrade via ester hydrolysis and that for Chol 2 -SS-G2 disulfide degradation, enhanced by DTT could also be detected. In combination, these assays demonstrate that rapid disulfide cleavage in the presence of DTT leads to triggered disassembly 75 and loss of SAMul binding of DNA. The products, which have released their grip on DNA, are then able to slowly degrade further into smaller fragments through an ester hydrolysis mechanism, which does not operate if DNA is still bound to the dendrons.…”
mentioning
confidence: 82%
“…To study the multivalent molecular recognition that characterizes the complexation, the binding between siRNA and dendrimers in a 1:1 ratio was modeled according to a validated strategy reported for the binding of dendrons and dendrimers with DNA [26, 27] and siRNA [28]. The structures of F2-2 , F3 and F4–2 were composed of different residues according to previous studies on similar dendrimers [22].…”
Section: Methodsmentioning
confidence: 99%
“…Polyamines such as putrescine, spermidine, and spermine as well as their derivatives have attracted considerable interest due to their biological functions and pharmacological properties [30][31][32][33][34][35]. Recently, gene delivery, especially that using nonviral synthetic vectors which were based on polyamine block, has attracted considerable interest [36][37][38][39][40][41][42]. The polyamine homopolymer behaves as a weak polybase at higher pH values, whereas at lower pH H. Wang : X. Ren : H. Zhang : Y. Tan values, the amine groups are protonated, and the polymer behaves as a cationic polyelectrolyte.…”
Section: Introductionmentioning
confidence: 99%